Relevansi Gagasan Pencalonan Presiden dan Wakil Presiden Jalur Perseorangan terhadap Prinsip Negara Hukum dan Demokrasi - Yuniar Riza Hakiki (Fakultas Hukum Universitas Jambi, 2020)
This article discusses the relevance of the for nominating the President and Vice President through the individual based on the principles of rule of law and democracy in Indonesia. Article 6A paragraph (2) of the 1945 Constitution of the Republic of Indonesia restricts the nomination of the President and Vice President of the Republic of Indonesia in a way that it can only be proposedby political parties or a combination of political parties. In other words, it limits individual candidate. As a country that adheres to the principles of the rule of law and democracy, various channels of democracy as a means of actively participating in politics must naturally be open widely. Therefore, the recruitment system for the positions of President and Vice President needs to be redesigned in line with principles of rule of law and democracy in Indonesia. This article concludes that the idea of ​​the for nominating the President and Vice President through the individual channels is by the principles of the rule of law and democracy, which is at least proven by the four arguments based on of the rule of law principles and democracy. First, guaranteeing the constitutional rights of citizens in political field. Second, guaranteeingself-actualization of citizens in political life independently (without being mobilized). Third, guaranteeing political recruitment to fill positions holding the state openly. Fourth, guarantee that the constitutional-based government is accommodative and remains organized according to law. Abstrak Artikel ini membahas relevansi pencalonan Presiden dan Wakil Presiden melalui jalur perseorangan atas dasar prinsip negara hukum dan demokrasi di Indonesia. Pasal 6A ayat (2) UUD NRI 1945 membatasi pencalonan Presiden dan Wakil Presiden Republik Indonesia yaitu hanya dapat diusulkan oleh partai politik atau gabungan partai politik. Hal itu menutup kesempatan pencalonan dari jalur perseorangan. Sebagai negara yang menganut prinsip negara hukum dan demokrasi, berbagai kanal demokrasi sebagai sarana berpartisipasi politik secara aktif dalam pemerintahan tentu harus terbuka lebar. Oleh karenanya, rekrutmen jabatan Presiden dan Wakil Presiden ini perlu didesain ulang agar lebih akomodatif dan selaras dengan prinsip negara hukum dan demokrasi Indonesia. Artikel ini menyimpulkan bahwa gagasan pencalonan Presiden dan Wakil Presiden melalui jalur perseorangan berkesesuaian dengan prinsip negara hukum dan demokrasi, yang setidaknya dibuktikan dengan empat argumen yang merujuk prinsip negara hukum dan demokrasi. Pertama, menjamin hak konstitusional warga negara di bidang politik. Kedua, menjamin aktualisasi diri warga negara dalam kehidupan politik secara mandiri (tanpa digerakkan). Ketiga, menjamin rekrutmen politik untuk mengisi jabatan-jabatan penyelenggaran negara secara terbuka. Keempat, menjamin pemerintahan yang berdasarkan konstitusi secara akomodatif berdasarkan hukum.